Evaluation of the Effects of Cluster Numbers Removal on Embryo Emergence of Central Asian Seedless Grape Varieties (Plant Tissue Culture and Biotechnology, 2025)
The potential for embryo rescue is one of the problems in the seedless grape breeding program. The majority of seedless grape types in nature are stenospermocarpic forms, which mostly cause seed abortion after fertilization. In this investigation, four seedless grape cultivars (Vitis vinifera L.) were hybridized to evaluate the effects of genotype and removing cluster number on embryo survival. The present findings indicated that removing of clusters does not affect to embryo number whereas the berry number and berry mass were significantly increased, however, a posteriori analysis showed the significance of differences in the number of clusters and berries between Kishnish Sogdiana and Kishmish Terakli varieties only and in the mass of berries - between the raisins of Kishnish Sogdiana and Belya Rosa. Finally, it can be concluded that embryo survival depends on genotype of seedless verities and therefore, the application of embryo rescue should be based on more scientific studies using several varieties of cultivars of grape.Plant Tissue Cult. & Biotech. 35(1): 163-176, 2025 (June)